2021
DOI: 10.1016/j.scitotenv.2020.144296
|View full text |Cite
|
Sign up to set email alerts
|

Wildland firefighter exposure to smoke and COVID-19: A new risk on the fire line

Abstract: Throughout the United States, wildland firefighters respond to wildfires, performing arduous work in remote locations. Wildfire incidents can be an ideal environment for the transmission of infectious diseases, particularly for wildland firefighters who congregate in work and living settings. In this review, we examine how exposure to wildfire smoke can contribute to an increased likelihood of SARS-CoV-2 infection and severity of coronavirus disease (COVID-19). Human exposure to particulate matter (PM), a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 75 publications
(65 reference statements)
0
36
0
2
Order By: Relevance
“…Other studies and reviews have reported that exposure to wildfire smoke in firefighters are associated with significantly greater risk of respiratory infections such as pneumonia and acute bronchitis (Navarro et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies and reviews have reported that exposure to wildfire smoke in firefighters are associated with significantly greater risk of respiratory infections such as pneumonia and acute bronchitis (Navarro et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Viability/survival of SARS Cov2/Covid 19 has been estimated at 9 h for hands as compared to influenza (another RNA respiratory virus) of 1.8 h (Hirose et al 2020 ). Some studies have suggested that particulate pollution may increase airborne survival of many types of viruses times by binding to bacteria and providing protection from UV light and by reducing dehydration (Navarro et al 2021 ; Reche et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Wildfire pollution health impacts are likely the greatest amongst proximate communities and for exposed minority and impoverished "essential" worker populations whose employment requires significant outdoor time, largely without appropriate protection (N95 mask). Of particular concern is wildfire firefighter smoke exposure, which could lead to higher Covid19 risk and who currently only use cloth masks for protection [17]. On a local level, by analogy, biomass or wood burning in homes for aesthetics, heating, or cooking may be increasing risks for homeowners and their neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance for potential hazards of oxygen therapy must be maintained. There is speculation that lung injury may be multiplicative from the combination of smoke inhalation and SARS-CoV-2 [9], but no prior case has been reported.…”
Section: Discussionmentioning
confidence: 99%